The Effect Of Leadership And Work Environment On Teacher Satisfaction With Motivation As A Moderating Variable In Methodist School Pelita Kasih Medan - Teddy, Teddy; Ronny Edward, Yusuf; Romy, Elly; Faris, Salman (CV. Inara, 2022)
This study aims to determine the effect of leadership and work environment on teacher satisfaction through motivation as a constraint variable. The object of research is the Pelita Kasih Methodist School in Medan. The population in this study were 30 teachers at the Pelita Kasih Methodist School in Medan using the population sampling method. The analytical method used is structural equation modeling with partial least squares (SEM-PLS). The results of this study indicate that leadership and work environment have a significant influence on teacher satisfaction. It is evident that motivation is not able to strengthen or weaken the relationship between leadership and work environment in relation to teacher satisfaction.